تحديات الأمن الغذائي في الجزائر وسبل تحقيقه - بن موسى, كمال; قويسي, مبروك (جامعة الوادي - University of Eloued, 2022)
تهدف هذه الدراسة إلى إلقاء الضوء على موضوع حساس وذو أهمية خاصة بالنسبة للدول النامية، التي يشكل قطاع الزراعة ومن ورائه السياسة الزراعية والغذائية دافعا لتحقيق الأمن الغذائي لشعوبها، وهو ما يدفع بنا إلى محاولة تسليط الضوء على واقع الأمن الغذائي في الجزائر، حيث أن دراسة وتحليل هذا الموضوع من مختلف جوانبه سيساعد في إيجاد حلول واقعية ومحاولة التحكم في المشاكل الناجمة عن عدم تحقيق الأمن الغذائي، وتحديد أهم المهددات خاصة الجديدة منها التي تقوض هذا الأمن لاسيما في الفترة الأخيرة، وما يقتضيه من ضرورة انتهاج أسس سليمة ووضع سياسات زراعية إستراتيجية دقيقة ومحددة وذات أهداف واقعية وعقلانية تفضي إلى تحسين الأمن الغذائي والمساهمة في ترقية وتطوير الإنتاج الزراعي. This study aims to shed light on a sensitive topic of special importance for developing countries, for which the agricultural sector and the agricultural and food policy behind it constitute a motive to achieve food security for their people, which prompts us to try to shed light on the reality of food security in Algeria, as the study and analysis of This issue in its various aspects will help in finding realistic solutions and trying to control the problems resulting from the failure to achieve food security, and identifying the most important threats, especially new ones that undermine this security, especially in the recent period, and the necessity of adopting sound foundations and setting accurate, specific and strategic strategic agricultural policies. Realistic and rational goals conducive to improving food security and contributing to the promotion and development of agricultural production.
Keywords: الأمن الغذائي، الفجوة الغذائية، الغذاء، الزراعة، السياسات الزراعية.